De l’intérêt de développer la notion de symbiose dans l’étude du hygge et de la famille danoise - Solène Mignon (Enfances, Familles, Générations, 2021)
Research framework: During my fieldwork with a Danish family where I studied the daily practices of family hygge (Danish well-being), my emic status changed from “au pair” to “big sister”. To understand this transformation, I decided to show the hygge-family association as symbiotic. Objectives: This paper aims to develop the notion of symbiosis so as to describe hygge-family relationships. In particular, I studied and questioned the often vague concept of hygge, which is sometimes associated with values and in other occasions with a Danish domestic and family way of life. This will allow us to understand the consequences of this symbiosis on my role and status within the family. Methodology: The article is based on participant observation and introspection in the sense of reflexive return on a nine-month fieldwork in a Danish family with three children (a father, a mother, a seven-year-old girl and three-year-old twins) in Hillerød. Results: Two empirical arguments underline the relevance of the notion of symbiosis: the observation of parenting practices and the analysis of the Danish child’s representations. The use of symbiosis also highlights a theoretical interest and helps to better grasp my role and place in the family. Contribution: Through the notion of symbiosis, this article brings forth another viewpoint of the Danish family and hygge. It also allowed for a reflexivity of the anthropologist’s practices on the field.